1996
DOI: 10.1097/00007632-199608010-00007
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation and Mobilization of the Cervical Spine

Abstract: Cervical spine manipulation and mobilization probably provide at least short-term benefits for some patients with neck pain and headaches. Although the complication rate of manipulation is small, the potential for adverse outcomes must be considered because of the possibility of permanent impairment or death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
184
1
23

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(212 citation statements)
references
References 74 publications
4
184
1
23
Order By: Relevance
“…49 As the ROM improved, the pain was also reduced. 50 Ice was used as a counterstimulation to help to relieve spasm and pain. 51 Galvanic current was used to reduce pain by inhibiting nociceptor activity and reducing edema.…”
Section: Discussionmentioning
confidence: 99%
“…49 As the ROM improved, the pain was also reduced. 50 Ice was used as a counterstimulation to help to relieve spasm and pain. 51 Galvanic current was used to reduce pain by inhibiting nociceptor activity and reducing edema.…”
Section: Discussionmentioning
confidence: 99%
“…11,13 However, a comparison of estimated serious complication rates from the various treatment approaches suggests that CMT is a reasonable option. Although mild or transient symptoms after CMT is fairly common, 21 the risk of vertebral artery injury and potential for cerebrovascular insult has been estimated at between 1 in 500 000 to 1 in 1 million 22 and 1 in 5.85 million. 23 In contrast, Gabriel et al 24 estimated the risk of serious gastrointestinal complications related to nonsteroidal anti-inflammatory use to be as high as 8 in 100; and Graham 25 found the risk for serious neurologic complications from posterior approach cervical surgery to be as high as 5.65 per 100.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of CNP is not yet fully understood [1,2]. Manual therapy is potentially a promising avenue for the management of CNP; yet, as several meta-analyses indicate, the efficacy of manual approaches has yet to be conclusively supported [2][3][4]. In a previous pilot trial, we showed that computerized mobilization of the cervical spine confined to the sagittal plane is a safe and potentially effective treatment of CNP.…”
Section: Introductionmentioning
confidence: 99%